Voltage Synchronization in Arrays of Fractional-order Energy Storage Elements - Hartley, Tom T. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, the balancing of a collection of electric energy storage devices is considered. Specific devices discussed are capacitors, supercapacitors, and batteries. The balancing problem is formulated as a complex network with dynamic nodes. The connection problem is approached from a graph theory viewpoint and solved by using homogeneous or entangled graphs. The utility of this approach is demonstrated with several examples